(untitled) (Canadian Journal of Counselling and Psychotherapy, 2020)
Social justice is becoming an increasingly important aspect of counselling psychology in Canada, and more research is needed to understand how to make a difference outside of one-on-one counselling sessions. Twelve individuals (including students, researchers, clinicians, and professors) comprised a working group entitled “The Responsibility of Canadian Counselling Psychology to Reach Systems, Organizations, and Policy-Makers” and discussed the role of counselling psychology in reaching beyond individual change. Discussion generated three main themes: identifying needs, using our unique training, and infiltrating and navigating the system. Future directions for social justice and advocacy in counselling psychology are discussed in relation to systemic change.